DEVELOPING GEOBOARD LEARNING MEDIA FOR STUDENTS’ MATHEMATICAL UNDERSTANDING ABILITY AT ELEMENTARY SCHOOLS - Kris Aflia; Yuyu Yuhana; Trian Pamungkas Alamsyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the feasibility of Geoboard media and to examine students' mathematical understanding after implementing Geoboard media in grade IV mathematics learning at SDN Serang 11. Geoboard media is a teaching tool designed to help elementary students understand geometry concepts, including plane figures, area, and perimeter. This research applied a Research and Development (R&D) method with stages consisting of problem analysis, data collection, product design, design validation, design revision, and limited trials. The results showed that the Geoboard media, designed like a chessboard, received validation scores of 90% from material experts, 88% from media experts, and 93.5% from students’ responses, which were categorized as very appropriate. The use of Geoboard media effectively improved students’ mathematical understanding, as evidenced by an average score above the KKM (81.75%). The final product was deemed highly suitable, efficient, and attractive as a learning media for teaching plane figures in grade IV mathematics.